An Integrated Inventory of Terrestrial and Marine Biodiversity in the Extreme South of Madagascar - Nirina Holongoe; Charles Mahafake; Emanuel Miandrireny Todisoa Tsiorenandraha; Liasinorie Kazy; Jean Alphonse Todisoanjanahary; Merci Mahatradraza; Sylvain Mahazotahy (Ite Ngabdi, 2026)
This study aims to provide an integrated inventory of terrestrial and marine biodiversity in the extreme south of Madagascar by documenting taxonomic diversity, endemism, species distribution, and conservation status across major biological groups. An integrated biodiversity assessment was conducted through a synthesis of published and unpublished literature, institutional records, and field inventories undertaken in representative terrestrial and coastal ecosystems of the Androy region. The study covered marine algae, mollusks, crustaceans, insects, amphibians, reptiles, tortoises, birds, lemurs, and other mammals. The findings revealed that the region supports considerable biological diversity despite its semi-arid environment, with particularly high levels of endemism among marine algae, mollusks, reptiles, birds, and lemurs. Several endemic and threatened species were identified, highlighting the ecological significance of the remaining dry forests, xerophytic thickets, and coastal habitats. However, biodiversity is increasingly threatened by habitat degradation, unsustainable resource use, illegal wildlife exploitation, prolonged drought, and climate change. This study provides one of the first comprehensive syntheses of biodiversity in the Androy region and establishes an important scientific baseline for future ecological research, biodiversity monitoring, conservation planning, and the sustainable management of Madagascar's unique natural heritage